Optimal Design and Analysis of 4.7 μm Hybrid Deep Dielectric High Efficiency Transmission Gratings - Ye Wang; Xiuhua Fu; Yongyi Chen; Hangyu Peng; Li Qin; Yongqiang Ning; Lijun Wang (Micromachines, 2022)
There is currently no transmission grating with good diffraction efficiency in the 4.7 μm band. Metal gratings at this wavelength are all reflective gratings which has a diffraction efficiency of lower than 90% and lower laser damage threshold. In this paper, we bring up a design of a multi-layer transmission grating with both high diffraction efficiency and wide working wavelength band. We have proved that the transmission grating made of composite materials has an average diffraction effectiveness of more than 96% throughout the whole spectral range of 200 nm. Meanwhile, the theoretically computed transmission grating has a highest first-order diffraction efficiency of more than 99.77% at 4746 nm. This multilayer dielectric film transmission grating’s optimized design may further boost spectral beam combining power, providing a practical technique for increasing SBC power and brightness.